2014
DOI: 10.21608/sjfop.2014.4110
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum and Gaillardia as Stunted Winter Annuals I. Tricolor Chrysanthemum (Chrysanthemum Carinatum Schousb.)

Abstract: Chrysanthemum carinatum Schousb. is a tall annual herb with a thin, weak stems suffers from slanting, but it is used excessively in Egypt for beautifying of beds and borders. So, a study was conducted at Orman Botanical Garden, Giza, Egypt during 2012/2013/2014 seasons to reveal the effect of foliar spraying with either paclobutrazol (PP-333) at the rates of 0, 50 and 100 ppm or cycocel (CCC) at the rates of 0, 1000 and 2000 ppm, twice with 3 weeks interval on growth performance, flowering and quality of 75-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…On other ornamentals, Mahmoud et al, (2008), noticed that PP-333 at 50 ppm level raised chlorophyll a and b content in the leaves of pinched and nonpinched oleander plants, while pinching alone caused a significant reduction in pigments, indoles and phenols content. Adversely, Shahin et al, (2014) found that PP-333 at 50 or 100 ppm concentration increased the leaf ( 104 ) content of chlorophyll a, b, carotenoids, total soluble sugars, indoles and phenols in Chrysanthemum carinatnm winter annual herb plant. On Russelia equisetiformis prepared to use as a pot plant, Abou-Dahab et al (2015) demonstrated that pinching treatment for two times raised chlorophyll a and carotenoids content to maximum, while chlorophyll b and phenols content was slightly increased, but indoles content was greatly decreed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On other ornamentals, Mahmoud et al, (2008), noticed that PP-333 at 50 ppm level raised chlorophyll a and b content in the leaves of pinched and nonpinched oleander plants, while pinching alone caused a significant reduction in pigments, indoles and phenols content. Adversely, Shahin et al, (2014) found that PP-333 at 50 or 100 ppm concentration increased the leaf ( 104 ) content of chlorophyll a, b, carotenoids, total soluble sugars, indoles and phenols in Chrysanthemum carinatnm winter annual herb plant. On Russelia equisetiformis prepared to use as a pot plant, Abou-Dahab et al (2015) demonstrated that pinching treatment for two times raised chlorophyll a and carotenoids content to maximum, while chlorophyll b and phenols content was slightly increased, but indoles content was greatly decreed.…”
Section: Discussionmentioning
confidence: 97%
“…On other ornamentals, many reports were decided by Auda et al, (2002) on Barleria cristata, Barett et al, (2003) on Petunia hybrida and Catharanthus roseus, Shahin et al, (2006) on Rudbeckia hirta, ( 95 ) Mahmoud et al, (2008) on Nerium oleander, Asgarian et al, (2013) on Zinnia, Shahin et al, (2014) on Chrysanthemum carinatum, Noor El-Deen et al, on Gaillardia pulchella, Abou-Dahab et al, (2015) on Russelia equisetiformis, Narayan (2015) on Tagetes erecta, El-Sadek (2016) on Hibiscus rosa-sinensis cv. Yellow, Zamani et al, (2016) on rosemary and Thuja "Morgan" Heikal (2017) on Sanchezia nobilis, Mohammed et al, (2017) on Lagerstroemia indica, Deniz and Omer Faruk (2018) on Fuchsia, Tawila (2018) on Celosia cristata, Naine et al, (2019) on ornamental pepper, Dong et al, (2020) on Paeonia lactiflora, Noor El-Deen (2020) on Ruellia simplex, Shahin and Moustafa (2021) on Althaea rosea and Noor El-Deen and Abou Elghait (2022) on Hibiscus rosasinensis cv.…”
Section: Introductionmentioning
confidence: 99%